Integrative Model of Reputation: One Construct, Four Dimensions - Inostroza González, Claudio Alejandro (Ediciones UNL. Secretaría de Extensión de la UNL, 2019)
The literature review on Management does not reach consensus regarding the concept of reputation. This suggests that the construct has a multidimensional structure that incorporates interactions and relationships of multiple attributes, which are perceived by stakeholders. Existing approaches usually address organizational reputation from a specific dimension. This research analyzes reputation as a strategic resource from the perspective of Resource Based View to propose a theoretical model that incorporates four dimensions in its evaluation: prominence, legitimacy, quality and distinctive aspects. The model can be used to manage reputation, managing each of its four perspectives. Understanding relationships between dimensions allows the organization to have a general picture of the situation in which their reputation is located and to know which aspects should be reinforced.